Seed Science and Technology 2023
DOI: 10.1007/978-981-19-5888-5_4
|View full text |Cite
|
Sign up to set email alerts
|

Seed Vigour and Invigoration

Abstract: Seed vigour is an important aspect of seed quality. It is a quantitative trait which is responsible for overall seed performance in terms of rate and uniformity of seed germination, seedling growth, emergence ability under unfavourable environments and post storage performance. Seed vigour is controlled by genetic factors, initial seed quality, production environments, harvesting and storage conditions. Seed vigour tests provide a more sensitive index of seed performance per se than the germination test. Effor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 72 publications
0
1
0
1
Order By: Relevance
“…The control seeds were discovered to have the lowest vigour index, seedling growth, and seed germination rates at the same period. In several crops, seed priming has been shown to have positive impacts on stand establishment, quick, uniform, and increased germination, improved seedling vigour and growth under a wide range of environmental conditions, and a decrease in phytochromeinduced dormancy [19][20][21][22]. When seeds are primed for germination, physiological tests have shown that their metabolic activity is boosted [23].…”
Section: Resultsmentioning
confidence: 99%
“…The control seeds were discovered to have the lowest vigour index, seedling growth, and seed germination rates at the same period. In several crops, seed priming has been shown to have positive impacts on stand establishment, quick, uniform, and increased germination, improved seedling vigour and growth under a wide range of environmental conditions, and a decrease in phytochromeinduced dormancy [19][20][21][22]. When seeds are primed for germination, physiological tests have shown that their metabolic activity is boosted [23].…”
Section: Resultsmentioning
confidence: 99%
“…The seed vigor index measures overall seed performance, including the rate and uniformity of seedling growth, emergence in unfavorable conditions, and post-storage viability. High temperatures during seed development and maturation can greatly reduce seed vigor, resulting in lower seed quality [18]. High temperatures can cause significant physiological damage to seeds, resulting in reduced seed vigor.…”
Section: Influence Of Different Treatments On Seed Vigour Index I and Iimentioning
confidence: 99%
“…Perlakuan perendaman dalam air 12 jam lalu dikeringkan 4 jam dalam oven suhu 38-40 ˚C tidak berbeda dengan taraf lainnya diduga perendaman dengan pengunaan aerator belum berfungsi secara maksimal disebabkan volume air dalam perendaman benih masih dalam batas normal benih untuk mampu melakukan respirasi dalam air. Menurut Basu (1994) manfaat dari perlakuan hidrasi-dehidrasi yang yaitu dapat memperbaiki sistem enzimatik seluler yang telah menurun aktivitasnya akibat usia benih selama penyimpanan sebelumnya, dan dapat meminimalisasi reaksi radikal bebas dan reaksi peroksidasi lipid dalam benih yang mengakibatkan proses kemunduran benih.…”
Section: Pengaruh Hidrasi-dehidrasi Terhadap Vigor Benihunclassified